Effectiveness of single and double phototherapy on indirect hyperbilirubinemia in neonates - Nanda Susanti Milyana; Guslihan Dasa Tjipta; Muhammad Ali; Emil Azlin; Bugis Mardina Lubis; Pertin Sianturi; Bebi Sofiani Hasibuan (Indonesian Pediatric Society, 2011)
Background Hyperbilirubinemia is a common problem in full term newborns and phototherapy is the most widespread treatment for lowering bilirubin concentration in neonates. Double phototherapy could increase the effectiveness of treatment.Objective To compare the effectiveness of single and double phototherapy and increasing spectral irradiance for decreasing serum bilirubin levels in neonates for indirect hyperbilirubinemia.Methods An open, randomized, controlled trial was conducted at H. Adam Malik and Pirngadi Hospitals, Medan, from May to December 2009. Subjects were divided into two groups, those who received single phototherapy (n=30) and those who received double phototherapy (n=30) treatments. We included term newborns with neonatal jaundice in the first week of life. Serum bilirubin and average spectral irradiation levels were measured at baseline and after 12 hours and 24 hours of phototherapy treatment.Results The mean total bilirubin levels of the single and double phototherapy groups at the beginning of therapy were 17.6 mg/dL (SD1.41) and 17.5 mg/dL (SD 1.32), respectively, with no significant difference between values. During the study period the sum of average spectral irradiance by double phototherapy was significantly higher than that of single phototherapy (P < 0.05). A significantly greater decrease in bilirubin levels was observed in the double phototherapy group at 12 hours and 24 hours of phototherapy compared to the single phototherapy group (P = 0.001).Conclusion Double phototherapy is more effective than single phototherapy in reducing bilirubin levels in jaundiced newborns.